2022
DOI: 10.3389/fphar.2022.812065
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Metabolism, and Excretion of ACT-1004-1239, a First-In-Class CXCR7 Antagonist: In Vitro, Preclinical, and Clinical Data

Abstract: ACT-1004-1239 is a potent, selective, first-in-class CXCR7 antagonist, which shows a favorable preclinical and clinical profile. Here we report the metabolites and the metabolic pathways of ACT-1004-1239 identified using results from in vitro and in vivo studies. Two complementary in vitro studies (incubation with human liver microsomes in the absence/presence of cytochrome P450- [CYP] specific chemical inhibitors and incubation with recombinant CYPs) were conducted to identify CYPs involved in ACT-1004-1239 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Previous clinical investigations revealed that ≥25% of ACT‐1004‐1239 elimination goes through the primary metabolite M1, which is predominately formed by CYP3A4. 2 Therefore, a DDI study with ACT‐1004‐1239 and a strong CYP3A4 inhibitor is recommended by health authorities to investigate the extent of an increase in ACT‐1004‐1239 exposure associated with CYP3A4 interactions. There are several strong CYP3A4 inhibitors that have been previously used as perpetrator drugs in DDI studies such as ketoconazole, ritonavir, or voriconazole.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous clinical investigations revealed that ≥25% of ACT‐1004‐1239 elimination goes through the primary metabolite M1, which is predominately formed by CYP3A4. 2 Therefore, a DDI study with ACT‐1004‐1239 and a strong CYP3A4 inhibitor is recommended by health authorities to investigate the extent of an increase in ACT‐1004‐1239 exposure associated with CYP3A4 interactions. There are several strong CYP3A4 inhibitors that have been previously used as perpetrator drugs in DDI studies such as ketoconazole, ritonavir, or voriconazole.…”
Section: Discussionmentioning
confidence: 99%
“…Such alternative routes may include the elimination through CYP2C19, CYP2C8, and CYP1A1, which were shown to also catalyze formation of M1 in vitro or other elimination pathways such as reduction of ACT‐1004‐1239 to the metabolite A3 as reported previously. 2 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations